Tingkat Keterdedahan Media Massa dan Perilaku Ber-Kb pada Keluarga Pra-Sejahtera di Pedesaan dan Perkotaan - Asri Sulistiawati; Anna Fatchiya; Aditya Rahmadhony; Diah Puspita Sari (Jurnal Penyuluhan, 2021)
The service and provision of free family planning (FP) for people belonging to the Pra-Prosperous and Prosperous I is an effort to increase community participation in family planning in order to reduce the TFR figure. In general, this study aims to analyze the behavior of family planning in pre-prosperous and prosperous families, which are divided into two regional characteristics; rural and urban areas. Furthermore, this study seeks to reveal the effect of mass media exposure on behavior change. The research was carried out with a quantitative approach through a survey method which was carried out on 120 households in two different locations: West Bogor District, Bogor City and Gunung Sindur District, Bogor Regency. The results showed that most of the couples of childbearing ages (Pasangan Usia Subur/PUS) had not been exposed to the mass media, especially information regarding family planning. The level of exposure to the mass media did not have a significant effect on changes in the behavior of PUS because respondents still relied on information sourced from extension workers and cadres.